Hubungan Motivasi Belajar dan Respon Siswa Terhadap Pembelajaran Hidrokarbon Menggunakan Chemsketch - Jesi Jecsen Pongkendek; Dewi Natalia Marpaung (Faculty of Teacher Training and Education, Musamus University, 2021)
The impulse that arises in students to be able to learn well is called learning motivation. Student response is a tendency arising from students towards learning that is applied. This research is a quantitative study to determine the correlation between learning motivation and response to hydrocarbon learning using Chemsketch. The study was conducted at SMAN 2 Merauke in Class XI Science 1 with 28 students. The sampling technique is simple random sampling. The research data were obtained using a questionnaire of learning motivation and student responses. The research data were analyzed descriptively and the results were obtained: (1) student motivation: 11 people (40%) were in the very high category and 17 people (60%) were in the high category, (2) student responses: 12 people (43% ) is in the very good category and 16 people (57%) are in the good category. Quantitative data analysis by testing the correlation between learning motivation and learning outcomes with the assumption of data linearity assumptions and data normality. After analyzing the results obtained that (1) there is a linear and significant relationship, (2) data is normally distributed, (3) there is a significant relationship between learning motivation and student response